Pengaruh Model Pembelajaran STEM di Era Revolusi Industri 4.0 terhadap Kemampuan Berpikir Kritis Siswa SMAN 5 Palu - Dewi Tureni; Aan Febriawan; Rizka Fardha; Amalia Buntu (Universitas Tadulako, 2021)
This research aims to determine the effect of the STEM Learning Model in the era of the industrial revolution 4.0 on students’ critical thinking skills of SMAN 5 Palu. The research method used is quasi-experimental with a population of all students at SMAN 5 Palu as many as 201 students. The sampling technique was purposive sampling, where class XI IPA 3 was the control class and class XI IPA 4 was the experimental class. The data analysis technique used t test with the help of SPSS 16 software for windows. The data collection technique used a description test instrument. The results of data analysis obtained in the experimental class / STEM obtained an average critical thinking score of 72.9 better than the control class / lecture 60.8, and the results of the t-test Tcount Ttable = 6.805 1.997. So it can be concluded that there is an influence of the STEM Learning Model on students' critical thinking at SMAN 5 Palu.